The claustrum : structural, functional, and clinical neuroscience - Smythies, John; Edelstein, Lawrence; Ramachandran, Vilayanur S.; ScienceDirect eBooks (San Diego, CA : Academic Press, 2014)
Of the Evidence from Expression of Calcium-Binding Proteins.
The present day is witnessing an explosion of our understanding of how the brain works at all levels, in which complexity is piled on complexity, and mechanisms of astonishing elegance are being continually discovered. This process is most developed in the major areas of the brain, such as the cortex, thalamus, and striatum. The Claustrum instead focuses on a small, remote, and, until recently, relatively unknown area of the brain. In recent years, researchers have come to believe that the claustrum is concerned with consciousness, a bold hypothesis supported by the claustrum's two-w.
History of the study and nomenclature of the claustrum -- The structure and connections of the claustrum -- The neurochemical organization of the claustrum -- Development and evolution of the claustrum -- Physiology of the claustrum -- Neurocomputation and coding in the claustrum -- Structural and functional connectivity of the claustrum in the human brain -- Delayed development of the claustrum in autism -- The claustrum in schizophrenia -- Clinical relations: epilepsy -- The claustrum and Alzheimer's disease -- Parkinson's disease and the claustrum -- Hypotheses relating to the function of the claustrum -- What is it to be conscious? -- Selected key areas for future research on the claustrum.
Includes index.
Print version record.
Elsevier
Keywords: Claustrum; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Claustrum; Electronic books